Crystal structure of (−)-flavesine H, C15H22N2O2 - Peng Kai; Luo Ding; Wang Guang-cun (Zeitschrift für Kristallographie - New Crystal Structures)
C15H22N2O2, monoclinic, P21 (no. 4), a = 8.4853(2) Å, b = 19.5759(4) Å, c = 9.0640(2) Å, β = 106.845(2)°, V = 1441.00(6) Å3, Z = 4, R gt(F) = 0.00374, wR ref(F 2) = 0.0991, T = 150 K.